Case Report: A Novel Homozygous Mutation in MYF5 Due to Paternal Uniparental Isodisomy of Chromosome 12 in a Case of External Ophthalmoplegia With Rib and Vertebral Anomalies - Li, Qianqian; Zhu, Xiaofan; Yu, Chenguang; Shang, Lin; Li, Ranran; Wang, Xia; Yang, Yaping; Meng, Jingjing; Kong, Xiangdong (Frontiers in Genetics, 2022)
External ophthalmoplegia with rib and vertebral anomalies (EORVA) is characterized by congenital nonprogressive external ophthalmoplegia, ptosis, scoliosis, torticollis, vertebral, and rib anomalies, caused by homozygous mutations in the myogenic factor 5 gene (MYF5) located on chromosome 12q21.31. Uniparental disomy (UPD) is a rare inheritance of a pair of chromosomes originating from only one parent. This study describes a case of an 8-year-old boy with blepharoptosis, scoliosis, and ribs with dysmorphic and fusion anomalies. Trio-based exome sequencing (trio-ES) identified a novel homozygous mutation c.191delC (p.Ala64Valfs*33) in MYF5 in the proband, with the father being heterozygous and the mother wild-type, as verified by Sanger sequencing. UPD identified from trio-ES variant call format data suggested the possibility of paternal UPD of chromosome12 (UPD12pat) in the proband, further confirmed to be a complete isodisomy type of UPD by genome-wide single nucleotide polymorphism array. MYF5 was significantly downregulated by 69.14% (**P < 0.01) in HeLa cells transfected with mutant MYF5 containing c.191delC compared to those transfected with the wild-type MYF5 resulting in a truncated protein with a size of ~20 kDa. In conclusion, this study identified a novel homozygous mutation in MYF5, broadening the genetic spectrum of EORVA and further deepening the understanding of this rare disease.